The second gamma-H2AX assay inter-comparison exercise carried out in the framework of the European biodosimetry network (RENEB). (2nd January 2017) - Moquet, Jayne; Barnard, Stephen; Staynova, Albena; Lindholm, Carita; Monteiro Gil, Octávia; Martins, Vanda; Rößler, Ute; Vral, Anne; Vandevoorde, Charlot; Wojewódzka, Maria; Rothkamm, Kai
Abstract: Purpose: Within the EU RENEB project, seven laboratories have taken part in training and harmonisation activities to strengthen triage gamma-H2AX-based radiation exposure assessment. This has culminated in a second triage biodosimetry exercise. Materials and methods: Whole blood and separated lymphocyte samples were homogenously irradiated with 60 Co gamma rays at 0.5, 2.5 (blind samples), 0 and 2 Gy (reference samples). Following post-exposure incubations of 4 and 24 h, 16 samples were shipped on ice packs to each partner. The samples were stained and scored for gamma-H2AX foci, using manual and/or automated fluorescence microscope scoring strategies. Dose estimates were obtained and used to assign triage categories to the samples. Results: Average dose estimates across all the laboratories correlated well with true doses. The most accurate assignment of triage category was achieved by manual scoring of the 4-h blood and lymphocyte samples. Only three samples out of a total of 46 were miscategorized in a way that could have adversely effected the clinical management of a radiation casualty. Conclusions: This inter-comparison exercise has demonstrated that following a recent acute radiation exposure, the gamma-H2AX assay could be a useful triage tool that can be successfully applied across a network of laboratories.